Pengelolaan sampah menjadi kompos di tpa talangagung, malang: inovasi berkelanjutan untuk lingkungan yang lebih baik - Syarafina, Ainassabih Liwani (Maliki Interdisciplinary Journal, 2025)
The increasing volume of waste in line with population growth and human activities poses a serious challenge to the environment, especially when not managed properly. Organic waste is a type of waste that decomposes easily and has the potential to be reused through the composting process. This article aims to examine the organic waste management system into compost at the Talangagung Final Processing Site (TPA) in Malang Regency. The study was conducted using an exploratory method and literature review with a qualitative approach. TPA Talangagung implements a controlled landfill concept and the 3R principles (reduce, reuse, recycle), and utilizes commercial bioactivators (EM4) and natural starters in the composting process. This process produces high-quality compost that can be used as organic fertilizer. In addition to ecological and agronomic benefits, this system also provides economic and educational impacts for the community. This study shows that the innovation in organic waste management at TPA Talangagung is a sustainable practice that can serve as a model for environmental management in other regions.